Health and socioeconomic implications of reliance on gasoline-generators for business activities in Ibadan, Nigeria (2014)
Nigeria’s crises of development are more evident in her persistently poor electric power regime. This paper focuses on the consequences of use of gasoline generators as alternative source of energy among business operators in Ibadan. Data were collected from 543 questionnaire responses, 15 In-depth Interviews and 6 Focus Group Discussions. Findings revealed that 83.6 percent of the respondents often utilized gasoline generators and 76.8 percent could not do without it. While the respondents perceived headache, cough, catarrh and respiratory tract infection as major health consequences, reduction in profit (33.7 percent) and low sales/service delivery (25.2 percent) were identified as negative economic effects of reliance on generators. Their coping strategies included regular medical check-up, nose-mask and bulk sales. Intensifying efforts at stabilizing electric power supply will go a long way to improving the health and socio-economic conditions of small and medium scale entrepreneurs and ultimately sustainable development.